Sources of nitrous oxide emissions from hydroponic tomato cultivation: Evidence from stable isotope analyses - Karlowsky, Stefan; Buchen-Tschiskale, Caroline; Odasso, Luca; Schwarz, Dietmar; Well, Reinhard (Frontiers in Microbiology, 2023)
Hydroponic vegetable cultivation is characterized by high intensity and frequent nitrogen fertilizer application, which is related to greenhouse gas emissions, especially in the form of nitrous oxide (N2O). So far, there is little knowledge about the sources of N2O emissions from hydroponic systems, with the few studies indicating that denitrification could play a major role. Here, we use evidence from an experiment with tomato plants (Solanum lycopersicum) grown in a hydroponic greenhouse setup to further shed light into the process of N2O production based on the N2O isotopocule method and the 15N tracing approach. Gas samples from the headspace of rock wool substrate were collected prior to and after 15N labeling at two occasions using the closed chamber method and analyzed by gas chromatography and stable isotope ratio mass spectrometry. The isotopocule analyses revealed that either heterotrophic bacterial denitrification (bD) or nitrifier denitrification (nD) was the major source of N2O emissions, when a typical nutrient solution with a low ammonium concentration (1-6 mg L-1) was applied. Furthermore, the isotopic shift in 15N site preference and in δ18O values indicated that approximately 80-90% of the N2O produced were already reduced to N2 by denitrifiers inside the rock wool substrate. Despite higher concentrations of ammonium present during the 15N labeling (30-60 mg L-1), results from the 15N tracing approach showed that N2O mainly originated from bD. Both, 15N label supplied in the form of ammonium and 15N label supplied in the form of nitrate, increased the 15N enrichment of N2O. This pointed to the contribution of other processes than bD. Nitrification activity was indicated by the conversion of small amounts of 15N-labeled ammonium into nitrate. Comparing the results from N2O isotopocule analyses and the 15N tracing approach, likely a combination of bD, nD, and coupled nitrification and denitrification (cND) was responsible for the vast part of N2O emissions observed in this study. Overall, our findings help to better understand the processes underlying N2O and N2 emissions from hydroponic tomato cultivation, and thereby facilitate the development of targeted N2O mitigation measures.